2004
DOI: 10.1096/fj.03-0610com
|View full text |Cite
|
Sign up to set email alerts
|

Multiple types of skeletal muscle atrophy involve a common program of changes in gene expression

Abstract: Skeletal muscle atrophy is a debilitating response to starvation and many systemic diseases including diabetes, cancer, and renal failure. We had proposed that a common set of transcriptional adaptations underlie the loss of muscle mass in these different states. To test this hypothesis, we used cDNA microarrays to compare the changes in content of specific mRNAs in muscles atrophying from different causes. We compared muscles from fasted mice, from rats with cancer cachexia, streptozotocin-induced diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

95
1,363
16
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,374 publications
(1,500 citation statements)
references
References 88 publications
(147 reference statements)
95
1,363
16
26
Order By: Relevance
“…Furthermore, we found that all three TGFbs are fibrogenic and placed P311 as a stimulator of fibrosis acting immediately upstream of TGF-b1 to -b3. Because P311 expression is up-regulated or down-regulated by hormones, 52 retinoic acid, 53 growth factors, 54 and mechanical tension, 4 and because P311 has proven to be decreased in muscular atrophy 55,56 and pulmonary emphysema, 6 it is likely that in pathologic conditions with decreased P311 expression scar formation will be affected in ways similar to those presented in this study, leading thereby to a higher risk of dehiscence.…”
Section: Resultssupporting
confidence: 51%
“…Furthermore, we found that all three TGFbs are fibrogenic and placed P311 as a stimulator of fibrosis acting immediately upstream of TGF-b1 to -b3. Because P311 expression is up-regulated or down-regulated by hormones, 52 retinoic acid, 53 growth factors, 54 and mechanical tension, 4 and because P311 has proven to be decreased in muscular atrophy 55,56 and pulmonary emphysema, 6 it is likely that in pathologic conditions with decreased P311 expression scar formation will be affected in ways similar to those presented in this study, leading thereby to a higher risk of dehiscence.…”
Section: Resultssupporting
confidence: 51%
“…Skeletal muscle atrophy could be due to reduced protein synthesis and/or increased protein catabolism due to targeted ubiquitination of muscle-specific proteins. Two muscle-specific E3 ligases, Atrogin1 and MuRF1, are up-regulated in skeletal muscle tissue in response to numerous atrophic signals [31][32][33]. Western blot analysis confirmed that there is increased ubiquitination of intracellular proteins in skeletal muscle tis-…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Inmentioning
confidence: 81%
“…E3 ligases, of which hundreds have been identified, confer substrate specificity (Glass, 2003a). During muscle atrophy, many of the genes encoding the Ub-proteasome pathway are upregulated , including E2 (such as E2 14K and UbcH2) and E3 (such as E3a / UBr1) genes (Li et al, 2003;Lecker et al, 2004). In particular, two E3 ubiquitin ligases, MuRF1 (muscle ring finger 1) and MAFbx (muscle atrophy F-box or atrogin-1) have been identified as mediators of muscle atrophy (Bodine et al, 2001a;Dehoux et al, 2003).…”
Section: Fibre Types: Coordinated Isoform-specific Expressionmentioning
confidence: 99%